Flight - Lopez, Donald (ed). 1832-1898.; Sir, 1820-1914 (New York Time Life Books, 1995)
Atmospheric illustrations, strong photographs and text encourage readers to discover for themselves the world around them.
Issued also with marginal illustrations.
Keywords: Aeronautics; Flight; Airplanes; Discoveries Library; Time-Life Books